2013
DOI: 10.1177/0969733012468462
|View full text |Cite
|
Sign up to set email alerts
|

Ethical problems and moral sensitivity in physiotherapy

Abstract: This study identified and described ethical problems encountered by physiotherapists in their practice and physiotherapists' moral sensitivity in ethical situations. A questionnaire-based survey was constructed to identify ethical problems, and the Moral Sensitivity Questionnaire Revised version was used to measure moral sensitivity. Physiotherapists (n = 116) working in public health services responded to the questionnaire. Based on the results, most of the physiotherapists encounter ethical problems weekly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
3
32
0
4
Order By: Relevance
“…1,16 Compared with younger and less experienced nurses, older and more experienced nurses had higher ethical sensitivity, possibly because they were more familiar with nursing care. 7,8,25 In line with previous studies, 16,19 we also found significant difference by clinic wards, which may be a surrogate for beliefs and behaviors. For example, surgical nurses were more prone to act in a materialistic manner, which may impede their ethical sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…1,16 Compared with younger and less experienced nurses, older and more experienced nurses had higher ethical sensitivity, possibly because they were more familiar with nursing care. 7,8,25 In line with previous studies, 16,19 we also found significant difference by clinic wards, which may be a surrogate for beliefs and behaviors. For example, surgical nurses were more prone to act in a materialistic manner, which may impede their ethical sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…Also use previous student reflections, critical incidents, and ethics research findings to develop authentic case studies. Use empirically based cases (Bushby et al 2015, Flatley, Kenny, and Lincoln 2014, Kulju, Suhonen, and Leino-Kilpi 2013, Praestegaard and Gard 2013.…”
Section: Case Studiesmentioning
confidence: 99%
“…These concern e.g. incompatibility of available resources and patient's needs [3,9,10], unethical behavior of physiotherapists or other professionals and realization of patients' autonomy [3,10]. Also close physical and emotional relationship between the patient and the physiotherapist creates specific ethical issues [11,12], such as how to maintain a professional proximity in the close and very often continued relationship.…”
Section: Introductionmentioning
confidence: 99%